2017
DOI: 10.2147/ijn.s127206
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of very small superparamagnetic iron oxide nanoparticles in murine organotypic hippocampal slice cultures and the role of microglia

Abstract: Superparamagnetic iron oxide nanoparticles (SPIO) are applied as contrast media for magnetic resonance imaging (MRI) and treatment of neurologic diseases despite the fact that important information concerning their local interactions is still lacking. Due to their small size, SPIO have great potential for magnetically labeling different cell populations, facilitating their MRI tracking in vivo. Before SPIO are applied, however, their effect on cell viability and tissue homoeostasis should be studied thoroughly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Hippocampal slice culture is widely used as a simplified, advantageous system in vitro for studying regeneration and neurodegeneration [ 27 ]. Organotypic hippocampal slice culture is similar to in vivo models, offering the possibility of analyzing neurogenesis and neuronal circuits, and is simpler compared to the neocortex [ 28 ]. In this study, we investigate the protective effect of quercetin on H 2 O 2 -induced apoptosis in PC-12 cells and organotypic hippocampal slice using TUNEL assay.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal slice culture is widely used as a simplified, advantageous system in vitro for studying regeneration and neurodegeneration [ 27 ]. Organotypic hippocampal slice culture is similar to in vivo models, offering the possibility of analyzing neurogenesis and neuronal circuits, and is simpler compared to the neocortex [ 28 ]. In this study, we investigate the protective effect of quercetin on H 2 O 2 -induced apoptosis in PC-12 cells and organotypic hippocampal slice using TUNEL assay.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the biocompatibility of nanoparticles with microglia has been widely studied, amidst serving as a sensitive marker to evaluate the toxicity of exogenous toxicants. 38 , 39 The results indicated that rh-EPO-Tw-ABNPs had no toxicity on the brain and nerve cells.…”
Section: Resultsmentioning
confidence: 94%
“…Microglia are important imaging targets for studying the inflammatory response after stroke ( 61 ). The region where USPIO aggregation causes signal changes on magnetic resonance images represents the activated microglia aggregation region ( 62 ). While ferumoxytol has a long half-life in blood, its half-life is only 45 min in mice, and previous studies have shown that almost no ferumoxytol is present in cerebral vessels 24 h after injection ( 63 ).…”
Section: Discussionmentioning
confidence: 99%